Se/S enhanced room-temperature phosphorescence of organic polymers. (November 2021) - Li, Zitong; Ding, Bingbing; Liu, Xiaoqin; Sun, Linbing; Ma, Xiang
Abstract: Room-temperature phosphorescence (RTP) materials have drawn widespread attention due to its unique property and extensive application, which makes finding effective ways to improve luminescence performance of RTP materials an urgent thing. We have prepared a series of polymers containing S/Se-naphthalimide derivatives that not only showed decent RTP properties in solid state, but also achieved RTP in aqueous solution. The heavy-atom effect of Se and hetero-atom effect of S can facilitate the spin-forbidden transfer of singlet-to-triplet excited states through intersystem crossing to populate triplet state thereby enhancing the RTP. The hydrogen-bonded crosslinking network of polymer systems endow the phosphorescence the good oxygen barrier property in both solid and aqueous states. This RTP-enhancing concept can lay a good foundation for the subsequent development of RTP materials with better performance. Graphical abstract: A series of polymers containing S/Se-naphthalimide derivatives have been prepared which processed decent room-temperature phosphorescent (RTP) performance. By enhancement of S/Se, the longest RTP lifetime of these materials up to 45.84 m s with orange afterglow, the highest total luminescence quantum yield is 30.9 % and their phosphorescence also can be detected in aqueous solution. Image 1 Highlights: Using Se/S as heavy atoms to adjust RTP behaviors in polymer system. RTP of S/Se-containing polymer both in solid states and aqueous solutions. Proper oxygen-resistance of aqueous RTP.